The Effect of a High‐Fat Meal on the Pharmacokinetics of Ixazomib, an Oral Proteasome Inhibitor, in Patients With Advanced Solid Tumors or Lymphoma. (17th March 2016) - Gupta, Neeraj; Hanley, Michael J.; Venkatakrishnan, Karthik; Wang, Bingxia; Sharma, Sunil; Bessudo, Alberto; Hui, Ai‐Min; Nemunaitis, John
Abstract: Ixazomib is the first oral proteasome inhibitor to be investigated in the clinic. This clinical study assessed whether the pharmacokinetics of ixazomib would be altered if administered after a high‐calorie, high‐fat meal. In a 2‐period, 2‐sequence, crossover study design, adult patients with advanced solid tumors or lymphoma received a 4‐mg oral dose of ixazomib as immediate‐release capsules on day 1 without food (fasted, administered following an overnight fast) or with food (fed, following consumption of a high‐calorie, high‐fat meal), followed by another dose on day 15 in the alternate food intake condition (fasted to fed or fed to fasted). Twenty‐four patients were enrolled; of these, 15 were included in the pharmacokinetic‐evaluable population. Administration of ixazomib after a high‐fat meal reduced both the rate and extent of absorption of ixazomib. Under fed conditions, the median time to peak plasma concentration (Tmax ) of ixazomib was delayed by approximately 3 hours compared with administration in the fasted state (1.02 hours vs 4.0 hours), and there was a 28% reduction in total systemic exposure (area under the curve, AUC) and a 69% reduction in peak plasma concentration (Cmax ). Together, the results support the administration of ixazomib on an empty stomach, at least 1 hour before or at least 2 hours after food. These recommendations are reflected in the United States Prescribing Information for ixazomib (clinicaltrials.gov identifier NCT01454076).